Importance of oligomerisation on Pseudomonas aeruginosaLectin-II binding affinity. In silico and in vitro mutagenesis - Wimmerová, Michaela; Mishra, Navnit Kumar; Pokorná, Martina; Koča, Jaroslav (Journal of molecular modeling, 2009)
The effect of terminal GLY114* deletion on the binding affinity of the PA-IIL lectin toward L: -fucose was investigated. Both experimental (isothermal titration calorimetry) and computational (molecular dynamics simulations) methods have shown that the deletion mutation decreases the L-fucose affinity. It implies that the PA-IIL saccharide binding affinity is influenced by the dimerization of the lectin. A detailed analysis of computational data confirms the key role of electrostatic interactions in the PA-IIL/saccharide binding.
Keywords: mutace; bakteriální adheziny; financování organizované; sekvenční delece; krystalizace; Kinetics; Protein Structure, Tertiary; Escherichia coli; počítačová simulace; Fucose; Protein Structure, Quaternary; Lectins; vazba proteinů; Binding, Competitive; terciární struktura proteinů; rekombinantní proteiny; Recombinant Proteins; Adhesins, Bacterial; Mutation; lektiny; Computer Simulation; Protein Multimerization; Models, Molecular; Financing, Organized; fukosa; molekulární modely; kalorimetrie; kompetitivní vazba; Pseudomonas aeruginosa; Calorimetry; Thermodynamics; kvarterní struktura proteinů; multimerizace proteinu; Crystallization; Sequence Deletion; termodynamika; Protein Binding; kinetika